2001
DOI: 10.1046/j.1365-2648.2001.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the self‐assessed support needs of women with breast cancer

Abstract: With the above three exceptions, women experienced a high level of need associated with a diagnosis of breast cancer. Studies of this kind should enable resources to be targeted to areas of highest need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 29 publications
2
43
2
8
Order By: Relevance
“…In a study by Cannon and Lindop in 2001 titled "assessment of support needs in breast cancer women" results showed that 97.5% of subjects considered needs associated with diagnosis important (Lindop and Cannon, 2001) which disagrees with results of the present study, and this could be due to the difference in cultures and age of the subjects, and discrepancy in the stage and type of treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In a study by Cannon and Lindop in 2001 titled "assessment of support needs in breast cancer women" results showed that 97.5% of subjects considered needs associated with diagnosis important (Lindop and Cannon, 2001) which disagrees with results of the present study, and this could be due to the difference in cultures and age of the subjects, and discrepancy in the stage and type of treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study by Lindop et al (2001), 97.5% of responding subjects considered diagnosis-related needs important (Lindop and Cannon, 2001). From all the above subjects, conclusion can be drawn that SASNs for women with breast cancer is a valid and reliable tool that can be used in clinical environments to screen perceived support needs of breast cancer patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Loss of a spouse also may contribute to a deficit in having physical needs met and dissatisfaction with decisions that had been made due to absence of a source of support. Lindop and Cannon (2001) found that acceptance of a changed appearance from a husband or partner was viewed as crucial to adjusting after a breast cancer diagnosis and support from a significant other is beneficial in decreasing psychosocial concerns especially when it is related to skin changes or loss of a body part. Furthermore, death of a spouse may be similar to the cancer experience described by rural patients in the Bettencourt (2007) study.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of a breast can therefore adversely impact upon body image, feelings of femininity, sexuality and sense of self (Falk Dahl et al, 2010;Manderson & Stirling, 2007). Following surgery, women can report feeling mutilated or like a part of them is missing (Kunkel et al, 2002;Lindop & Cannon, 2001). Mastectomy and scarring from surgery in particular, have also been found to have a profoundly negative impact on body image and feelings of sexuality (Sheppard & Ely, 2008).…”
Section: What Is the Impact Of An Altered Appearance For Women With Bmentioning
confidence: 99%